Business Communication Strategies for Organizations in Transition: A Systematic Review of Theory, Practice, and Organizational Performance - Lorence Manalu (Yayasan Aya Sophia Indonesia, 2025)
Rapid disruption in today's business environment requires organizations to adapt to change quickly and effectively. Effective business communication is an important factor in supporting organizations that are going through transition and change. This research aims to explore the relevance of Lewin's model in managing organizational change amid business disruption and analyze the role of business communication strategies in supporting organizational performance during transition. Using a systematic review method, this study collected and analyzed related literature from various academic sources. The results show that Lewin's model remains relevant to be applied in change management, although it requires adjustments in terms of more adaptive communication to handle the accelerating disruption. Open and transparent communication and leadership that supports employee engagement are proven to accelerate the change process and improve organizational performance during the transition. This study concludes that the integration of effective communication with Lewin's model can optimize the change process and improve organizational performance. Future research is recommended to explore digital communication and technology in supporting change management in large and complex organizations.